Web-based nutrition: a useful resource for cancer patients? - Lazar, Diana Elena; Postolica, Roxana; Hanganu, Bianca; Mocanu, Veronica; Ioan, Beatrice Gabriela (Frontiers in Nutrition, 2023)
Introduction An accessible and affordable way to deliver behavior change programs to a large proportion of the growing community of cancer patients and survivors is through web-based methods of nutritional counselling. Objective The aim of this systematic review was to evaluate the effectiveness of web-based nutritional therapies targeting physical activity, diet, and/or weight control for cancer patients or survivors, primarily disseminated via modern technologies (mobile phone applications) or online. Materials and methods The authors conducted a structured search of the PubMed database. Studies that have focused on physical activity (PA) and dietary change and/or weight control in adolescent and adult cancer patients and survivors have reported outcomes conducted via a broad modality. Results Nine articles focused on web-based nutrition for patients with cancer and cancer survivors. They were conducted in the United States, Australia, Korea, China, and in the United Kingdom, and were published between 2018 and 2022 in a variety of scientific journals. The number of participants ranged from 20 to 159. Conclusion Web-based nutrition counselling helps cancer patients and survivors improve their dietary intake, impacts their weight and quality of life, and promotes a healthy lifestyle. Future research should evaluate (1) the differences in cost and coverage between face-to-face and web-based nutrition, (2) long-term outcomes, (3) cost-effectiveness, and last but not least, (4) the effectiveness of web-based nutrition in adolescents and children who suffer from cancer or who survived cancer, as nutritional status and body composition have a marked impact on clinical outcomes during and after treatment. The strength of this review lies in the large number of randomized controlled trials, which offer a guarantee of effectiveness and objectivity compared to cross-sectional studies.